A OBSERVAÇÃO DE ALGUNS ASPECTOS ENUNCIATIVOS EM TRADUÇÕES DE APRENDIZES DE FRANCÊS: O CASO DE DES. - Zavaglia, Adriana (Intercâmbio, 2010)
This work aims at presenting some thoughts about enunciative aspects of the relation between language and natural languages in translation. We analyze the french-to-portuguese translations of a text made by brazilian students in different stages of their learning process.